Protestant Dissent and Philanthropy in Britain, 1660-1914 - Binfield, Clyde; Ditchfield, G. M.; Wykes, David L. (Melton : Boydell & Brewer, Incorporated, 2019)
Philanthropy was an essential feature of the relationship between Dissent and the society from which it sometimes felt itself to be separate.
7 Funding Faith: Early Victorian Wesleyan Philanthropy8 Unitarians and Philanthropy After 1844: the Formation of a Denominational Identity; 9 Children and Orphans: Some Nonconformist Responses to the Vulnerable in Victorian Britain; 10 The Rowntree Family and the Evolution of Quaker Philanthropy, c. 1880 to c. 1920; 11 'Not slothful in business': Enriqueta Rylands and the John Rylands Library; Select Bibliography; Index
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Charities -- Great Britain -- History -- 17th century; Charities -- Great Britain -- History -- 18th century; Endowments -- Great Britain -- History -- 17th century; Endowments -- Great Britain -- History -- 18th century; Dissenters -- Great Britain -- History -- 17th century; Dissenters -- Great Britain -- History -- 18th century; Great Britain -- Church history -- 17th century; Great Britain -- Church history -- 18th century; Fondations -- Grande-Bretagne -- Histoire -- 17e siècle.; Fondations -- Grande-Bretagne -- Histoire -- 18e siècle.; Dissidents -- Grande-Bretagne -- Histoire -- 17e siècle.; Dissidents -- Grande-Bretagne -- Histoire -- 18e siècle.; Grande-Bretagne -- Histoire religieuse -- 17e siècle.; Grande-Bretagne -- Histoire religieuse -- 18e siècle.; Charities; Dissenters; Endowments; Great Britain; 1600-1799; Electronic books; Church history; History